Strength, rate of force development, and force control evaluations to quantify upper-limbs asymmetries agreement in professional male volleyball players - D`Emanuele, S.; Boccia, G.; Zardo, V.; Durigon, V.; Schena, F.; Tarperi, C. (The Journal of Strength and Conditioning Research, 2025)
Asymmetries are known to vary based on the nature of the sport and differ between individuals and the tests used. We explored interlimb asymmetries in muscle function among 13 national-level male volleyball players (24 ± 3 years; 87 ± 7 kg; 194 ± 7 cm; 19 ± 2 hours training/week), aiming to determine whether these asymmetries are muscle specific and consistent across various metrics. Subjects underwent assessments for elbow extensors and flexors in both limbs, including maximal contractions to assess the maximal voluntary force (MVF), submaximal ballistic contractions measuring Rate of Force Development (RFDpeak), Scaling Factor (RFD-SF), and evaluations of Approximate Entropy (ApEn), Coefficient of Variations, and Detrended Fluctuation Analysis (DFAa) during sustained contractions. Repeated-mixed ANOVA within and between-factors assessed each metric's differences between muscle groups and limbs. Kappa coefficients (K) were calculated to determine the levels of agreement for the direction of asymmetry among muscle groups and different metrics at the individual level. Our findings revealed that asymmetries were muscle specific, with statistical significance observed only in flexors MVF (12%, p = 0.007, d = 0.68). The asymmetry direction agreement between metrics was null for all parameters except for MVF, which resulted in slight (K = 0.022) and fair (K = 0.308) for ApEn. The agreement between RFDpeak vs MVF (K = 0.386) was fair, slight between RFDpeak vs RFD-SF (K = 0.141), and null when comparing RFDpeak with ApEn and DFAa. At the individual level, no consistent performance advantage was found for either limb, despite volleyball's partial asymmetrical nature, emphasizing the importance of creating personalized training based on the muscle/limb of interest and the parameter to be improved (i.e., maximum strength or RFD).